Children's friendships in super-diverse localities: Encounters with social and ethnic difference. (February 2017) - Iqbal, Humera; Neal, Sarah; Vincent, Carol
This article explores how children make, manage, or avoid friendships in super-diverse primary school settings. We draw on interviews and pictorial data from 78 children, aged 8–9 years across three local London primary schools to identify particular friendship groupings and the extent to which they followed existing patterns of social division. Children in the study did recognise social and cultural differences, but their friendship perceptions, affections, conflicts and practices meant that the way in which difference impacted relationships was partial and unstable. Friendship practices in the routine settings of school involved interactions across difference, but also entrenchments around similarity.